Dominant Mode Wave Impedance of Regular Polygonal Waveguides. (6th February 2014) - Komarov, Vyacheslav V.
Abstract : Polygonal metal waveguides are analyzed analytically and numerically. Classical equation for the wave impedance of arbitrary shaped waveguides is completed with approximate expression for the cutoff wavelength of the dominant mode. Proposed approach is tested with the help of 3D finite difference time domain models of microwave waveguides junctions. Obtained data are used for computer-aided design of microwave transition from coaxial line to cylindrical waveguide.